2020
DOI: 10.1002/ange.201911477
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Nanomaterials for Photothermal Therapy

Abstract: Two‐dimensional (2D) nanomaterials are currently explored as novel photothermal agents because of their ultrathin structure, high specific surface area, and unique optoelectronic properties. In addition to single photothermal therapy (PTT), 2D nanomaterials have demonstrated significant potential in PTT‐based synergistic therapies. In this Minireview, we summarize the recent progress in 2D nanomaterials for enhanced photothermal cancer therapy over the last five years. Their unique optical properties, typical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 118 publications
0
76
0
1
Order By: Relevance
“…[63] Basically, 2D transition metal chalcogenides also have plasmonic properties in the NIR region, similar to other types of 2D PTA nanomaterials, and this is the main reason why they can be proposed as new PTAs. [64] Up till now, the most widely studied and commonly used 2D transition metal chalcogenide has been MoS 2; single-layered MoS 2 nanosheets produced good results in cancer PTT. Typically, Chou et al first prepared chemically exfoliated MoS 2 nanosheets as a new NIR PTA and the results demonstrated that the as-made MoS 2 nanosheets had an excellent ability for causing the photothermal-triggered death of cancer cells in vitro.…”
Section: Transition Metal-based Materialsmentioning
confidence: 99%
“…[63] Basically, 2D transition metal chalcogenides also have plasmonic properties in the NIR region, similar to other types of 2D PTA nanomaterials, and this is the main reason why they can be proposed as new PTAs. [64] Up till now, the most widely studied and commonly used 2D transition metal chalcogenide has been MoS 2; single-layered MoS 2 nanosheets produced good results in cancer PTT. Typically, Chou et al first prepared chemically exfoliated MoS 2 nanosheets as a new NIR PTA and the results demonstrated that the as-made MoS 2 nanosheets had an excellent ability for causing the photothermal-triggered death of cancer cells in vitro.…”
Section: Transition Metal-based Materialsmentioning
confidence: 99%
“…In PTT, the local heating of NIR-absorbing agents is triggered by NIR light illumination. As tumor cells have difficulty dissipating heat, the NIR-triggered photothermal effect causes selective death of cancerous cells, which can be ablated more than 42 °C through necroptosis and apoptosis, which is programmed cell death, while endowing little damage to normal cells [ 9 ]. In contrast, PDT is an indirect method using photosensitizers that generate harmful singlet oxygen ( 1 O 2 ) when they absorb light.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–3 ] These nanomaterials include noble metals, 2D nanocrystals and their families, such as graphene, graphene oxide, and MXenes. [ 3–9 ] They are modified to conjugate drugs and imaging agents for synergistic or theranostic cancer therapies. [ 3–9 ] Despite numerous in vitro and in vivo investigations, the biosafety of most nanomaterial‐based vehicles is disputed.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3–9 ] They are modified to conjugate drugs and imaging agents for synergistic or theranostic cancer therapies. [ 3–9 ] Despite numerous in vitro and in vivo investigations, the biosafety of most nanomaterial‐based vehicles is disputed. [ 10–13 ] Most nanocarriers are formulated by undesirable surfactants and stabilizers for preventing aggregation; some of them also cannot be degraded in vivo, thus their accumulation in the body arouses concerns.…”
Section: Introductionmentioning
confidence: 99%